Criminal mining on the Atabapo River border Colombian Venezuelan: proposals for a solution - Fonseca-Moreno, Andrea Catalina; Gualteros-Pinzón, Carlos Edgardo; González-Díaz, Jaime Eduardo (EFIM Ediciones, 2019)
The purpose of this article is to describe the phenomena of criminal mining in the river Atabapo territorial border with Venezuela, and present proposed solutions to this phenomenon. This is a descriptiveresearch product. It presents a diagnosis of inﬂuential aspects in the economic, social, political and military felds; and the eﬀects of these futures generated or not to have a policy for regulating such activity. On the economic side the mainly indigenous people have changed the way we sustain due to the generation of direct employment by groups active criminal mining, as well as the involvement of this activity on the issue of royalties. In the social aspect it is important to address the eﬀect on medium and long-term health of the population of the two countries caused by the dumping of elements such as mercury and cyanide. On the political side, ignorance of the area’s population concerning mining regulations, the impact on the sovereignty of the two countries given by the inﬂuence of man on the riverbed. In the military area currently and generally in this part of the border are groups outside the law are strategically located in the Colombian-Venezuelan border with the aim of consolidating tactical mobility corridors.